Parsnip—Pastinaca sativa L. - James M. Stephens (EDIS)
This document provides an overview of the parsnip (Pastinaca sativa L.), detailing its origins, cultivation practices, and use. It highlights the plant’s resemblance to carrots, its preference for cooler climates, and challenges in growing it in Florida. The text also discusses the plant’s historical significance, cultural adaptability, and storage considerations, including the common practice of waxing roots for retail sale. Original publication date May 1994.